Price-setting policy determinants: micro-evidence from Brazil - Marcelo L. Moura; José Luiz Rossi Júnior (Economia Aplicada, 2010)
The paper studies the frequency of price changes from a survey data on Brazilian companies. The data set has the advantage of including all of the economic sectors: agricultural and food products, trading, industry and services. Strong evidence of nominal price rigidities is found on the data with average and median price durations around 10.1 and 8.1 months, which is very close to results reported for the euro area and the United States. Using econometric modeling through an ordered probit and also an OLS regression, we find that price change duration is mostly explained by the wage duration, the degree of competition, product specialization, the elasticity of demand and economic sector dummies. The empirical results refute somewhat commonly used macroeconomic modeling for monetary policy evaluation; however they do not refute time-dependent models since those are consistent with different price durations across firms. These results shed light on some stylized facts that a macroeconomic price-setting model would need to reproduce.